Screening of colorectal cancer: present and future. Issue 12 (2nd December 2017) - Maida, Marcello; Macaluso, Fabio Salvatore; Ianiro, Gianluca; Mangiola, Francesca; Sinagra, Emanuele; Hold, Georgina; Maida, Carlo; Cammarota, Giovanni; Gasbarrini, Antonio; Scarpulla, Giuseppe
ABSTRACT: Introduction : Colorectal cancer (CRC) is the third most common cancer in males and second in females, and the fourth most common cause of cancer death worldwide. Currently, about 60–70% of diagnosed cases in symptomatic patients are detected at an advanced stage of disease. Earlier stage detection through the use of screening strategies would allow for better outcomes in terms of reducing the disease burden. Areas covered : The aim of this paper is to review the current published evidence from literature which assesses the performance and effectiveness of different screening tests for the early detection of CRC. Expert commentary : Adequate screening strategies can reduce CRC incidence and mortality. In the last few decades, several tests have been proposed for CRC screening. To date, there is still insufficient evidence to identify which approach is definitively superior, and no screening strategy for CRC can therefore be defined as universally ideal. The best strategy would be the one that can be economically viable and to which the patient can adhere best to over time. The latest guidelines suggest colonoscopy every 10 years or annual fecal immuno-chemical test (FIT) for people with normal risk, while for individuals with high risk or hereditary syndromes specific recommendations are provided.